Assessing the Efforts of Selected Pentecostal Churches in Solving the Problem of Drug Addiction among Youth in South-Western Nigeria - Emmanuel Olusegun Ayomide; Dairo, Afolorunso Olalekan; Adegbite, Doyinsola Deborah (Corpus Intellectual, 2025)
The prevalence of substance addiction among Nigerian youths, is quite alarming, despite all efforts made by the government and non-governmental organisations, the church inclusive, in South-western Nigeria to reduce the social menace. The study evaluates the efforts of Pentecostal churches in solving the vice among youths in South-western Nigeria.This research is fundamentally descriptive in its approach. The target demographic for this investigation encompassed the Pentecostal congregations located in the South-Western region of Nigeria, viz: Osun, Ekiti, Ogun, Oyo, Ondo, and Lagos states, predominantly inhabited by the Yoruba ethnic group. Two pentecostal churhes in this geo-political zone are chosen for this study, viz: the Redeemed Christian Church of God (RCCG) and Mountan of Fire and Miracles Ministries (MFM).It is concluded that drug addiction is prevalent among youths in the South- Western geo-political zone of Nigeria and that Pentecostal churches are active in curbing drug addiction among the churched and unchurched youths. Standing on the principle of collaborative efforts, the following suggestions were made: the National Drug Law Enforcement Agency should collaborate with non-governmental organisations and other stakeholders responsible for preventing drug addiction to strengthen their campaigns against drug addiction, particularly among young people, in order to create a drugfree society; parents should be actively encouraged to pursue drug education and teach their children this knowledge as an essential component of health, moral, and character development; and counselling centres should be established in every community by the government or private individuals.